Pendampingan Pengelolaan Keuangan UMKM di Masa Pasca Pandemi - Ani Setyowati; Scorina Dwiantari (Gapenas Publisher, 2022)
The Covid 19 pandemic that occurred in 2020 until now has had a significant impact on the business and financial conditions of all business sectors, especially in the field of Micro, Small and Medium Enterprises. The existence of MSMEs as contributors to gross domestic product cannot be underestimated because they are able to encourage the community's economy through the provision of jobs and income distribution when the government has limitations in providing employment opportunities. However, the Covid-19 pandemic has eroded the economic ability of MSMEs to continue to develop due to operational limitations from the implications of restricting community activities as instructed by the Government. Therefore, as the best solution for SMEs today, they must be able to manage finances in anticipation of unwanted conditions such as the condition during the Covid 19 Pandemic yesterday. The focus of the service is carried out at the Kurniawan Textile UMKM which is located in Tanjung Mas Village, North Semarang District. As a result of service, partners gain knowledge and skills in managing finances to determine business operations run by MSMEs.